Stock returns and risk: Evidence from quantile - Thomas C. Chiang; Jiandong Li (Journal of Risk and Financial Management, 2012)
This paper employs weighted least squares to examine the risk-return relation by applying high-frequency data from four major stock indexes in the US market and finds some evidence in favor of a positive relation between the mean of the excess returns and expected risk. However, by using quantile regressions, we find that the risk-return relation moves from negative to positive as the returns' quantile increases. A positive risk-return relation is valid only in the upper quantiles. The evidence also suggests that intraday skewness plays a dominant role in explaining the variations of excess returns.
Keywords: C12; C13; G10; G11; 330; Risk-return tradeoff; Volatility; Intraday skewness; Quantile Regression; High-frequency data